Implementation of a communication protocol between a geo-location database and TV white space devices - Dionísio, Rogério Pais (2013)
Television White Spaces (TVWS) are a spectral opportunity, for secondary users of the spectrum to deliver broadband access to rural areas. Most of the approaches now under test worldwide use a geo-location database to inform secondary users of the available channels, and avoid interference with primary users of the spectrum. The secondary network should follow a approach capable to communicate with a geo-location spectrum database, to store and retrieve information on spectrum occupancy, location of DVB-T broadcast towers and wireless microphones, maximum EIRP of secondary White Space devices (WSDs), sensing activity and other technical parameters. One group from the Internet Engineering Task Force (IETF) is presently working on the definition of a protocol to access white spaces databases – PAWS. The IETF draft protocol was chosen and considered flexible enough to be adapted for the CREW-TV project model and requirements, since it is more comprehensive and less specific on details than other proposals.